2008
DOI: 10.1016/j.rapm.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Intraneural Catheterization of the Sciatic Nerve In Humans: A Pilot Study

Abstract: Intraneural catheterization of the sciatic nerve may be a frequent finding and was not followed by nerve injury under the conditions of our small pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
1
13
0
2
Order By: Relevance
“…Indeed, conventional opacification probably lacks both sensitivity and specificity to assess with accuracy catheter tip location in close vicinity of a nerve. One part of the answer has perhaps been given in a recent study on popliteal stimulating catheters by Rodriguez et al 20 These authors showed very elegantly, using computed tomography, that when a low MIS is obtained during stimulating catheter insertion, the likelihood of an intraneural placement of the popliteal catheter increases. 20 We may then reasonably hypothesize that when using low MIS, some catheters might have been located under the epineurium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, conventional opacification probably lacks both sensitivity and specificity to assess with accuracy catheter tip location in close vicinity of a nerve. One part of the answer has perhaps been given in a recent study on popliteal stimulating catheters by Rodriguez et al 20 These authors showed very elegantly, using computed tomography, that when a low MIS is obtained during stimulating catheter insertion, the likelihood of an intraneural placement of the popliteal catheter increases. 20 We may then reasonably hypothesize that when using low MIS, some catheters might have been located under the epineurium.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients of STIM group presenting a successful block with a volume of 4 mL or less (ie, patients 11,13,14,17,18,20,22, and 24 of STIM group), median duration of surgical anesthesia was 225 mins (212Y246 mins).…”
Section: Surgical Anesthesiamentioning
confidence: 99%
“…The recent use of ultrasound for peripheral nerve blocks has shown that accidental intraneural puncture and intraneural injection of local anesthetic is a common feature [11]. This finding also has been confirmed by CT scan with perineural catheters inserted with nerve stimulation guidance [12]. Therefore, needle-induced injury of intraneural vessels is a real possibility that also must be considered.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3][4][5][6] Consequently, this has led to the suggestion that injecting small volumes of local anesthetic beneath the epineurium but outside the perineurium is an acceptably safe practice. 9 The report described here was associated with placement of a needle within a peripheral nerve and was associated with new neurological deficit despite the absence of an intraneural injection.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] This report concerns a case where a venous cannulation needle was placed into a patient's peripheral nerve. The event was associated with severe lancinating pain and subsequent neurological deficit.…”
Section: Résumémentioning
confidence: 99%